Physical training after heart valve replacement. Issue 6 (December 1980) - Newell, J P; Kappagoda, C T; Stoker, J B; Deverall, P B; Watson, D A; Linden, R J
Abstract : A controlled trial was undertaken to examine the efficacy of physical training in patients recovering from the replacement of a single heart valve. Patients were allocated to a test or control group two weeks after operation. Each patient performed a submaximal exercise test at entry, and 12 and 24 weeks after this test. The Canadian Air Force exercise programme was undertaken by the test group, while the control group continued normal activities for the 24 weeks between the first and last exercise group. A regression line of submaximal heart rate on oxygen consumption was calculated from the data of each exercise test in each patient. Alterations in this line were used as an "index" of changes in "cardiorespiratory fitness". The individual results showed a consistent improvement in "cardiorespiratory fitness" over the first 12 weeks in both groups. Only patients in the test group continued to improve between 12 and 24 weeks. Thus the exercise programme modified the recovery of "cardiorespiratory fitness" after operation. Results in patients who developed clinical complications, and were excluded from the trial, predicted a deteriorating clinical condition. This finding suggested that sequential exercise tests are of value after cardiac surgery.